Co-combustion of sewage sludge and Zhundong coal: Effects of combustion conditions on gaseous pollutant emission and ash properties. (December 2022) - Guo, Shuai; Gao, Jialiang; Zhao, Deng; Zhao, Chenchen; Li, Xingcan; Li, Guangyu
Highlights: Co-combustion of sewage sludge and Zhundong coal under various conditions was studied. The sludge mixing ratio was inversely correlated with SO2 emission. The specific surface area of ash was the largest at a sludge content of 20 wt%. A 20% sludge content and a temperature of 900 °C were the optimal co-fired conditions. Abstract: The combustion of sewage sludge (SS) generates large amounts of NO x and SO x, while that of alkali and alkaline earth metal-rich coals produces slagging-prone ash. To determine whether these problems can be mitigated through the co-combustion of SS and coal, we examined the effects of SS and Zhundong coal co-combustion in a horizontal tubular furnace on the emission of NO x and SO x, analyzing the micromorphology, composition, and pore structure of the produced ash. Sludge content was inversely correlated with SO2 emission but had little effect on NO x emission. A high sludge content promoted the fusion of ash particles, whose size was positively correlated with combustion temperature. Na/Ca-feldspar miscibility led to the fusion of ash particles, facilitating the production of magnesia-iron spinel and complex phosphates to alleviate slagging. The specific surface area of ash was negatively correlated with temperature and was the largest at a sludge content of 20 wt%. The fractal dimensions calculated to examine pore structure complexity and pore surface roughness revealed that the latter parameter was inversely correlated with temperature. A reaction temperature of 900 °C and sludge content of 20 wt% were optimal conditions for gaseous pollutant emissions and ash agglomeration behaviors during co-combustion. Thus, this study provides a theoretical basis for controlling the operation of coal/SS co-fired power plants in terms of pollutant emission, combustion efficiency, and ash slagging.